(untitled) (Revista Sistemas de Producción Agroecológicos, 2011)
Two experiments were conducted at the Universidad de los Llanos, Villavicencio (Meta), the main objective was to observe the productive performance of broilers that were given diets with different levels of Trichanthera gigantea flour (TF) and flour Erythrina poeppigiana (EF) (0, 5, 8 and 12%), replacing other sources of protein such as meat meal is traditionally used in poultry diets. The variables studied were: weight gain, consumption, conversion, biological value of protein, coefficient protein efficiency (CPE) and carcass yield. The chickens were distributed in a completely randomized design, consisting of four treatments in experiment one were: control (0% TF), Trichanthera I (5% TF), Trichanthera II (8% TF) III Trichanthera (12% TF), and in experiment two were: control (0%EF), Erythrina I (5% EF), Erythrina II (8% EF) and Erythrina III (12% EF). In the case of TF found that when levels were increased feed intake decreased (P<0,01), the same situation arose with the biological value, but the weight gain, and conversion were similar for witness and 5% of TF to be higher (P<0.01) compared to other treatments (62.9 grams/day/bird, 2.5; 65.0 grams/day/bird and 2.3, respectively). The CPE was better (P<0.01) for 5% of TF (2.7) compared to other treatments. Consumption of food and biological value of protein is not affected when levels increased pore diets, while weight gain was lower (P<0.01) for 12% of EF (50.2 grams/day/bird), the best conversions and the CPE had the witness and 8%EF (2.2 and 2.5, 2.0 and 2.4, respectively). The results of these experiments is concluded that TF and EF can be replaced in diets for broilers up to 5% and 8%, respectively, without adversely affecting the parameters studied, as well as in treatments containing more of these feed the birds showed an intense yellow color of the carcass with less fat compared with the control.